Upaya Meningkatkan Kepercayaan Diri Siswa Melalui Bimbingan Klasikal Berbasis Hubungan Sosial Teman Sebaya - Palma Pasolang; Alfrida Padang; Yosafat Rerung Pagirik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to synthesize various research findings regarding the role of peer support in increasing adolescent self-confidence and synthesize various guidance and counseling interventions and the role of social support in increasing self-confidence. The method used is a comprehensive review of the results of action research (PTBK), experiments, and correlational studies from various levels of education. The findings show that classical guidance services with Problem-Based Learning (PBL) and brainstorming methods, group guidance with creative media, peer support significantly increase students' courage in expressing opinions using a literature review from several scientific journals, this study analyzes how social interaction, peer counseling, and social support from peers contribute to the formation of positive self-concepts in students. The results can be seen that peer support plays a significant role in increasing adolescent self-confidence through various forms of support, such as respect for opinions, social acceptance, and positive interactions in groups. Adolescents who receive high social support from peers often have better courage and confidence than those with low support. This study provides implications that schools need to develop peer-based interaction programs to create an environment that supports students' psychological development. In conclusion, a holistic approach that combines professional services and strengthening the social environment is very effective for students' personal development.